Usaha Preventif Dm Gestasional Dan Anxiestas Pada Ibu Hamil - Margareta Haiti; Novita Anggraini; Lidwina Septie christyawardani; Aprida Manurung (IAI Darussalam, 2022)
Pregnancy is a physiological condition experienced by a woman who will give birth to the next generation. During pregnancy, a mother should perform Ante Natal Care (ANC) at least 4 times which aims to keep the mother and fetus healthy and avoid/prevent complications or complications during pregnancy, childbirth, the postnatal period and the baby to be born. Gestational Diabetes Mellitus (GDM) is one of the disorders that can occur in pregnant women. GDM can have a short-term and long-term impact on both the mother and the child. One of the effects is that the baby is big so that it can be difficult for pregnant women and childbirth which in turn can cause anxiety in pregnant women. Objective: Through this activity, it is hoped that pregnant women can understand the importance of checking blood sugar levels during pregnancy. Method: carry out counseling and health checks, including checking blood sugar levels.